# Solve for v -3/7v=-12 -37v=-12
Multiply both sides of the equation by -73.
-73⋅(-37)⋅v=-73⋅-12
Simplify both sides of the equation.
Simplify -73⋅(-37)⋅v.
Cancel the common factor of 7.
Move the leading negative in -73 into the numerator.
-73⋅(-37)⋅v=-73⋅-12
Move the leading negative in -37 into the numerator.
-73⋅-37⋅v=-73⋅-12
Factor 7 out of -7.
7(-1)3⋅-37⋅v=-73⋅-12
Cancel the common factor.
7⋅-13⋅-37⋅v=-73⋅-12
Rewrite the expression.
-13⋅-3⋅v=-73⋅-12
-13⋅-3⋅v=-73⋅-12
Cancel the common factor of 3.
Factor 3 out of -3.
-13⋅(3(-1))⋅v=-73⋅-12
Cancel the common factor.
-13⋅(3⋅-1)⋅v=-73⋅-12
Rewrite the expression.
-1⋅-1⋅v=-73⋅-12
-1⋅-1⋅v=-73⋅-12
Multiply.
Multiply -1 by -1.
1⋅v=-73⋅-12
Multiply v by 1.
v=-73⋅-12
v=-73⋅-12
v=-73⋅-12
Simplify -73⋅-12.
Cancel the common factor of 3.
Move the leading negative in -73 into the numerator.
v=-73⋅-12
Factor 3 out of -12.
v=-73⋅(3(-4))
Cancel the common factor.
v=-73⋅(3⋅-4)
Rewrite the expression.
v=-7⋅-4
v=-7⋅-4
Multiply -7 by -4.
v=28
v=28
v=28
Solve for v -3/7v=-12

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top